MASALAH YANG DIHADAPI SISWA DALAM PEMBELAJARAN DARING DIMASA PANDEMI COVID-19 SISWA KELAS V - Nurmala Sari; Budiman Tampubolon; Tahmid Sabri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to describe the problems faced by students in online learning during the Covid-19 pandemic in class V of 34 Pontianak City Elementary Schools. The method used in this research is descriptive qualitative method with the form of survey research. Data collection tools in this study used a questionnaire observation sheet, interview guides, and documentation. The results showed that in online learning students experienced several problems in learning. The problem experienced by students themselves is that students do not take the time to read books and repeat the material that has been given. Students do not do much learning activities because they are not with their teachers and friends. The last problem is that students are often given individual assignments by the teacher without clear explanations. In carrying out learning, the teacher carries out online learning using the WhatsApp application. Teacher assessment is only in the form of knowledge.Keywords: Learning Problem, Online Learning, The Pandemic